Material Consumption and Carbon Emissions Associated with the Infrastructure Construction of 34 Cities in Northeast China - Heming Wang; Yao Wang; Cong Fan; Xinzhe Wang; Yao Wei; Zhihe Zhang; Jiashi Wang; Fengmei Ma; Qiang Yue (Complexity)
Over the past three decades, China has experienced rapid economic growth along with a rapid increase in urbanization and living standards, leading to a boom in infrastructure demand. A large part of China’s newly constructed infrastructure is through urban construction; thus, cities have become a major source of material consumption and carbon emissions. Understanding the relationship between material consumption, carbon emissions, and the economic growth of cities is key to ensuring that the construction of infrastructure satisfies the needs for both economic development and dematerialization. In this study, we first accounted for material consumption and the carbon emissions of infrastructure construction of 34 cities in Northeast China and characterized spatial and temporal changes from 2010–2017. The material use and carbon emissions of infrastructure construction declined by 34.6% and 30.2% during this period. Specifically, material consumption decreased from 305.2 million tonnes to 199.6 million tonnes, and carbon emissions decreased from 77.7 million tonnes to 54.3 million tonnes. Furthermore, we used a decoupling indicator to evaluate the decoupling of material consumption or carbon emissions from GDP in these cities. We found that most cities have achieved the absolute decoupling of material consumption and carbon emissions from GDP over the study period. Finally, we proposed several policy recommendations for promoting the sustainable development of the infrastructure of cities. To ensure that cities realize low-carbon urbanization, policymakers need to promote modular buildings and low-emission construction materials. This paper also serves as a practical reference for the improvement of relevant materials and carbon emissions management strategies for other developing regions.